Dissecting Tissue Compartment-Specific Protein Signatures in Primary and Metastatic Oropharyngeal Squamous Cell Carcinomas - Sadeghirad, Habib; Monkman, James; Mehdi, Ahmed M.; Ladwa, Rahul; O’Byrne, Ken; Hughes, Brett G. M.; Kulasinghe, Arutha (Frontiers in Immunology, 2022)
Head and neck squamous cell carcinoma (HNSCC) often present with locoregional or distant disease, despite multimodal therapeutic approaches, which include surgical resection, chemoradiotherapy, and more recently immunotherapy for metastatic, or recurrent HNSCC. Therapies often target the primary and nodal regional HNSCC sites, and efficacy at controlling occult distant sites remains poor. Whilst our understanding of the tumour microenvironment, conducive for effective therapies is increasing, the biology underpinning locoregional sites remains unclear. Here, we applied targeted spatial proteomic approaches to primary and lymph node metastasis from an oropharyngeal SCC (OPSCC) cohort, to understand the expression of proteins within tumour, and stromal compartments of the respective sites in both matched and unmatched patients’ samples. In unmatched analyses of n=43 primary and 11 nodal metastasis, our data indicated that tumour cells in nodal metastases had higher levels of Ki-67, PARP, BAD and cleaved caspase 9, suggesting a role for increased proliferation, DNA repair and apoptosis within these metastatic cells. Conversely, in matched analyses (n=7), pro-apoptotic markers BIM and BAD were enriched in the stroma of primary tumours. Univariate, overall survival (OS) analysis indicated CD25 in tumour regions of primary tumours to be associated with reduced survival (HR=3.3, p=0.003), while partial response (PR) was associated with an improved OS (HR=0.33, p=0.015). This study highlights the utility of spatial proteomics for delineating tumour and stroma compartment composition, and the utility towards understanding these properties in locoregional metastasis. These findings indicate the unique biological properties of lymph node metastases that may elucidate further understanding of the subsequent distant metastatic potential of OPSCC.